PENGARUH ARUS KAS DARI AKTIVITAS OPERASI, INVESTASI DAN PENDANAAN, TERHADAP EXPECTED RETURN SAHAM PADA PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA - Suwetja, I Gede (Universitas Sam Ratulangi, 2014)
Under circumstances of uncertainty, the investors prefers to think rationally for considering about risk and expected return as theoretically have a straight line, because as the expected returns are higher, then the risk also become higher. The data of this study is using six automotive companies listed in Indonesia Stock Exchange in period of 2006 till 2010.Conducting path analysis, the findings of this study are partially the cash flow from investment activities has a significant effect to expected return for listed automotive companies in Indonesia Stock Exchange.